Discriminating Quartzite Sources Petrographically in the Upper Gunnison Basin, Colorado: Implications for Paleoamerican Lithic-Procurement Studies. (2nd January 2016) - Dalpra, Cody L.; Pitblado, Bonnie L.
Abstract : Archaeologists lack a protocol for systematically attributing quartzite artifacts to particular geologic sources of the material. This paper, in an effort to begin to remedy that situation, reports the preliminary results of a petrographic study of quartzite samples from the Upper Gunnison Basin (UGB), Colorado. In that region, the overwhelming predominance of quartzite (often > 90 per cent) at most archaeological sites has hampered efforts to ascertain with any certainty the mobility strategies of Paleoamerican (and later) residents. In this study, qualitative and quantitative characterization of texture and grain composition of 50 UGB quartzite specimens led to the identification of six statistically distinct groups of samples. The groups are not arbitrary divisions of the data set; rather, they are meaningful from geologic, geospatial, chronological, and human-behavioral perspectives.